An identification method for key geometric errors of machine tool based on matrix differential and experimental test. (December 2014) - Li, Dianxin; Feng, Pingfa; Zhang, Jianfu; Yu, Dingwen; Wu, Zhijun
This paper presents a key geometric errors identification method for machine tools based on matrix differential and experimental test. An error model for a machine tool was established by regarding the three-axis machining center as a multi-body system. The sensitivity coefficients of the machining error with respect to the geometric errors were determined using the matrix differential method, and the degree of influence of the geometric errors on the machining accuracy under ideal conditions was discussed. Using the 12-line method, 21 geometric errors of the machine tool were identified, allowing the three-dimensional volumetric error distributions of the machine tool to be mapped. Experimental results allow the degree of influence of the geometric errors on the machining accuracy under actual conditions to be confirmed. Finally, the key geometric errors affecting the machining accuracy were identified by a combination of matrix differential and experimental test. This paper provides guidance for the machine tool configuration design, machining technology determination, and geometric error compensation.